2007
DOI: 10.1016/j.ultrasmedbio.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D Imaging of Contrast Flow: Demonstration of a Dual Beam Technique

Abstract: Perfusion imaging in a 3D volume using ultrasound contrast agent may improve vascular characterization compared to 2D imaging. Conventional 3D acquisition requires excessive scan time. A dual transducer technique using conventional systems has been introduced that allows 3D imaging of contrast dynamics with drastically reduced scan times (LeCarpentier et al. 2003). Two transducers are translated across a volume where the leading transducer effects contrast clearance and the following transducer images at desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The kidney phantom was mounted beneath the water on a stand and secured with two elastic bands. As previously described (Chen et al 2007), a DT assembly was used to demonstrate the dual beam technique by controlling both transducer separation and translation along the transducers' elevational direction. Although two transducers were used for acquiring the volumetric images in this work, any setup composed of two independent beams, such as a two-dimensional array, could be used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kidney phantom was mounted beneath the water on a stand and secured with two elastic bands. As previously described (Chen et al 2007), a DT assembly was used to demonstrate the dual beam technique by controlling both transducer separation and translation along the transducers' elevational direction. Although two transducers were used for acquiring the volumetric images in this work, any setup composed of two independent beams, such as a two-dimensional array, could be used.…”
Section: Methodsmentioning
confidence: 99%
“…The dual-transducer (DT) technique illustrated earlier (Chen et al 2007) is one dual-beam method for collection of three-dimensional data. Sweeping a transducer pair, composed of a clearance transducer and a low-power imaging transducer as a unit at velocity v over a contrast perfused tissue volume collects the refill images of the entire volume at a given refill time as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Chen et al have recently demonstrated a dual-beam technique to achieve perfusion estimation using two dual planar imaging transducers; one for destruction, and one for imaging. 15, 16 Chen’s method, which was validated in-vitro, is proposed as a more rapid technique than the single-transducer approach described here, however, would be more challenging to implement in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…all of the presented techniques call for optimized and specialized processing to achieve an efficient and robust assessment of perfusion. For data acquisition in 3-d an approach is proposed in [29] using a dual beam technique. In the present paper, however, a fast approach of interleaving (with respect to the time axis of the TIc) is presented that is applicable to all presented techniques without special hardware [30], [31].…”
Section: Introductionmentioning
confidence: 99%